Design and Implementation of an IoT-Based Automatic Irrigation and Environmental Monitoring System for Amorphophallus muelleri (Porang) Cultivation - Harsuni, Resky; Laila, Ida; Abdullah, Bualkar; Arifin, Arifin (The Physical Society of Indonesia, 2026)
The cultivation of Amorphophallus muelleri (porang) in Indonesia is highly dependent on rainfall patterns and is influenced by environmental factors such as temperature, soil moisture, light intensity, and precipitation. This dependency often results in inefficient irrigation management and suboptimal plant growth. This study aims to develop an Internet of Things (IoT)-based automatic irrigation and environmental monitoring system specifically designed to support porang cultivation and improve water management efficiency. The system was implemented using an Arduino Uno microcontroller and a NodeMCU ESP8266, integrated with DHT22 (temperature and humidity), YL-69 (soil moisture), BH1750 (light intensity), and rain sensors, and connected to the Blynk IoT platform for real-time monitoring and remote control. Calibration results showed low measurement errors of 2.19%, 1.75%, and 5.09% for the temperature, soil moisture, and light intensity sensors, indicating reliable sensor performance. The test results showed that the system was able to automatically activate the water pump when soil moisture fell below the 50% threshold, thereby maintaining soil moisture within the optimal range under various environmental conditions. Overall, the proposed system enables continuous environmental monitoring and effective automatic irrigation control to support optimal porang growth.